“I CAN TAKE CARE OF MYSELF!”: UPAYA PENINGKATAN KAPASITAS KEMANDIRIAN REMAJA MELALUI PELATIHAN PERAWATAN DIRI MANDIRI DI JATIBARANG, INDRAMAYU - Rahmadianty Gazadinda; Gita Irianda Rizkyani Medellu; Santi Yudhistira; Gumgum Gumelar Fajar Rakhman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract The limitation of job opportunities in Indramayu has become one of the reason local citizen prefers to work outside Indramayu which leads to the family strengthening’s issue due to the facts that their children is left-behind with the extendend family during their leaving days. Although the main reason of this condition is for sorting the family financial’s issue, the children will be the one who is strongly affected due to the parental absence. The condition would be more challenging when their kids transformed into an adolescent since major life changing is happening. During the situation, parental presence would be very beneficial for the child however the condition might not be as ideal as it was expected. The “I can take care of myself!” program is presented to improve individual’s independency in taking care of themselves—or self-care. The program was held in SMP Negeri 1 Jatibarang, Indramayu and involved 35 students with no specific criterion. The program was evaluated twice by utilizing short questionnaire forms in order to identify participants’ understanding regarding how to face the major life changing and take care of themselves during adolescence phase. The evaluation found there is a significant different understanding about the strategy of self-care after the program delivered (t=2.478; sig. 0.019). This finding implicates that the training can increase individual’s comprehention in taking care of themselves—which hopefully can increase their independency in self-caring. Abstrak Terbatasnya kesempatan kerja di Indramayu menjadi alasan masyarakat memilih bekerja di luar Indramayu hingga berdampak pada ketahanan keluarga—terutama ketika anak ditinggalkan bersama anggota keluarga besar lainnya atau disebut juga left-behind children. Meskipun fenomena ini didasari usaha untuk memperbaiki perekonomian keluarga, anak akan sangat terdampak karena kehilangan sosok orang tua. Kondisi ini semakin berisiko ketika anak memasuki usia remaja—yang mana akan membutuhkan pendampingan dari orang tua dalam menghadapi perubahan diri. Pelatihan “I Can Take Care of Myself!” diberikan guna membantu meningkatkan kapasitas kemandirian remaja di Jatibarang, Indramayu melalui psikoedukasi tentang bagaimana menghadapi perubahan dan merawat diri di masa remaja. Pelatihan ini diadakan di SMP Negeri 1 Jatibarang, Indramayu selama satu hari dengan melibatkan 34 siswa tanpa kriteria khusus. Tim pengabdi mengevaluasi pemahaman peserta tentang strategi merawat diri sebelum dan setelah pelaksanaan pelatihan. Hasil evaluasi menunjukkan adanya peningkatan yang signifikan dalam hal pengetahuan tentang cara merawat diri di masa remaja (t=2.478; sig. 0.019). Temuan ini mengindikasikan pelatihan tersebut mampu meningkatkan pengetahuan remaja dalam merawat diri sehingga remaja di SMPN 1 Jatibarang diharapkan dapat lebih mandiri dalam merawat diri.